MAKNA ASOSIATIF DALAM FILM “MELUKIS KAKI LANGIT” KARYA GIRI PRASETYO BERDASARKAN PERSPEKTIF GEOFFREY LEECH - Wiwil Saputri; Abdul Muntaqim Al Anshory; Muhammad Ilham (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
This study analyzes the dialogues in the film Painting the Skyline by Giri Prasetyo which contain associative meanings. This article aims to know and identify the types of associative meanings in the film Painting Feet in the Sky based on the perspective of Geoffrey Leech. This research is a type of descriptive qualitative and library research with a semantic approach. This study used the listen-and-record technique. Data analysis techniques by reduction, presentation, and drawing conclusions of data. From this study, there are 4 out of 7 types of associative meanings, namely connotative meaning, stylistic meaning, affective meaning, and colloquial meaning. The connotative meaning contained in this film is 7 words, namely children who have grown up, live together, drift away, do not know the direction of the destination, nature, put hope, stop school. The stylistic meaning is 3 words, namely slumped, free, and remote—affective meaning of 3 words, namely obedient, saturated, and expressions of command. The colloquial meaning contained in the film Painting the Skyline by Giri Prasetyo is 3 words, namely family members, planets, and plants..